The Relationship Between Neurological Activity and /r/ Phoneme Pronunciation Disorders in a Neurolinguistic Perspective - Prastyo, Nada Tarofil Lubbi; Sholihah , Mujaahidatus; Khoiriyah , Wildatul; Mintowati, Mintowati; Solihin, Annas (Papanda Publisher, 2025)
Phoneme pronunciation disorder of the phoneme /r/ is one of the complex articulation problems and is often experienced by individuals across various age groups. This study aims to analyze the pronunciation disorder of the phoneme /r/ in 19-year-old individuals from a neurolinguistic perspective using a qualitative method. This case study utilizes direct observation and in-depth interviews as data collection techniques to understand articulation patterns, subjective experiences, and the factors influencing the disorder. The results show that the subject experienced distortion of the phoneme /r/, which appeared as a replacement with the phoneme /w/ or the loss of the /r/ sound in various word positions, especially in the initial and middle positions. Neurological activities that affect articulatory motor coordination play an important role in this disorder, further influenced by psychosocial factors such as social anxiety and environmental reactions. The subject also reported frustration and decreased self-confidence that impacted social interaction and motivation in therapy. These findings confirm the need for a therapeutic approach that integrates neurolinguistic stimulation and psychosocial support to improve the articulation function of the phoneme /r/. This study makes an important contribution to the development of neurolinguistic theory and speech therapy practice with a holistic approach that considers neurological, linguistic, and social aspects. Thus, the results of this study can serve as a basis for the development of more effective interventions to overcome /r/ phoneme pronunciation disorders in late adolescence.